Study of the impact of mRNA mistranslation in lipid homeostasis - Araújo, Ana Rita Dias (2017)
Erroneous mRNA translation (mistranslation) originates a statistical proteome. Previous studies in different model organisms proved that mistranslation is generally deleterious in standard growth conditions. Particularly in yeast, different types of amino acid misincorporation cause phenotypic diversity, including mitochondrial dysfunction, proteotoxic and oxidative stress, DNA damage, transcriptome deregulation, among others. Proteotoxic stress alone is known to trigger alterations in lipid metabolism. In agreement with these observations, the induction of amino acid misincorporation deregulates lipid metabolism-related genes. The link between mistranslation and lipid-related diseases has been also established, namely in the well-known Barth syndrome. However, the cellular processes affected in the case of several other diseases are still unclear. In this thesis, we attempted to elucidate the effects of mRNA mistranslation on the lipidome and showed the occurrence of altered lipid profiles. We expressed a recombinant seryl-tRNA gene in Saccharomyces cerevisiae in order to induce mistranslation. The anticodon of this tRNA was mutated to recognize alanine or glycine codons, and hence introduce serine at protein sites that normally correspond to alanine or glycine. Total lipid extracts analysed using a lipidomics approach revealed altered fatty acid, phospholipid and triacylglycerol species profiles. The same methods were used to analyse purified mitochondria. In this case, only the profiles of phospholipid species were altered. Functional and molecular studies, showed no evidence of increased oxidative stress; there were alterations in OLE1 expression, the gene that codes for a fatty acid desaturase. Mitochondrial function-related parameters were also tested and were altered. Finally, we sought to understand whether mRNA mistranslation impacted the genome, and in particular, we searched for mutations in lipid metabolism-related genes. For this, we evolved our strains for 250 generations and sequenced their genomes. Overall, the data show that serine misincorporation at alanine and glycine sites perturbs lipid homeostasis.